Urgensi Kompetensi Sosial Guru Dalam Meningkatkan Prestasi Peserta Didik di Madrasah Aliyah Ma’arif 7 Banjarwati Lamongan - ., Subekhi; ., Fathurrahman; Wahyudi, Winarto Eka; Muthoharoh, Miftakhul (TABYIN: JURNAL PENDIDIKAN ISLAM, 2022)
This study aims to determine the Social Competence of Teachers in Improving Learning Achievement in Madrasah Aliyah Ma'arif 7 Banjarwati Lamongan. The data collection techniques used are observation, interviews, and documentation studies. The results of this study are that the competencies possessed by teachers include competencies in terms of acting inclusively and objectively, as well as being non-discriminatory and adaptive. In addition, teachers in improving student presets, have a good construct in terms of achieving success both academic and non-academic, which is supported by social attitudes such as communication, cooperation and knowing the background of each student.